Mrs. Emma Chittich, Mrs. Earl Dailey and Mrs. Don L. Wade - Unknown:::Creator::::::::::::
Photograph shows (left-to-right) Mrs. Emma Chittich, Mrs. Earl Dailey, and Mrs. Don L. Wade. Mrs. Emma Chittich and Mrs. Earl Dailey are holding phonograph records while Mrs. Don L. Wade is reaching for one. There is a record player on the table they are standing around.